Pemberdayaan Ekonomi Masyarakat Lokal melalui Pelatihan Membatik di LPK Prima Cilegon - Masturi, Masturi; Maisaroh, Maisaroh; Makhilah, Hadyu; Akbari, Ari Adhariayani (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This study aims to examine the impact of a batik training program organized by LPK Prima Cilegon on community economic empowerment through a non-formal education approach. The program is designed to improve batik-making skills and foster entrepreneurship based on local potential. Using a descriptive qualitative method, data were collected through interviews, observations, and documentation. The results show that the training not only enhanced participants’ technical skills but also encouraged entrepreneurial spirit and expanded market access through digital platforms. The program had a positive impact on increasing income, strengthening social networks, and preserving local culture. The main targets of the program were women, housewives, and productive-age individuals without stable employment. Support from local government, industry, and community groups contributed to the program’s success as a participatory and sustainable model of skill-based economic empowerment.